Revisiting the typification of three names in the family Gentianaceae - Lahiri, Subhajit; Dash, Sudhansu Sekhar; Maity, Rohan (Phytotaxa, 2022)
Designated types of three pre-1958 validly published names in the family Gentianaceae are reassessed and lectotypes are designated for the names viz.: Gentiana micans C.B.Clarke, Gentiana phyllocalyx C.B.Clarke, and Swertia hookeri C.B.Clarke.